Impact of COVID-19 on the Egyptian economy: Economic sectors, jobs, and households - Breisinger, Clemens; Raouf, Mariam; Wiebelt, Manfred; Kamaly, Ahmed; Karara, Mouchera (International Food Policy Research Institute, 2020)
The COVID-19 crisis may lead to a 1.1 percent decline in Egypt’s GDP during the 4th quarter (April to June) of the 2019/20 fiscal year, compared to the same quarter in 2018/19. Without the Government of Egypt’s COVID-19 emergency response package, GDP in Q4 may have declined by 8.7 percent. Tak-ing the emergency response pack-age into account, we estimate an annual growth rate of 3.8 percent for FY 2019/20. Without the emer-gency response package, annual growth for FY 2019/20 may have been as low as 1.9 percent. The services sector is hit hardest, falling by 10.9 percent, followed by industry at -8.3 percent. Agriculture is the most resilient sector. However, these losses are lower than those expected in comparable countries, especially those that resorted to extended periods of full lockdowns. Impacts on Egypt’s agri-food system are less severe than elsewhere in the economy. Most damage will occur in nonfarm components of the agri-food system due to falling consumer demand. Although higher-income households face the largest income losses, lower-income households also will see their incomes decline significantly. The level of social protection required to fully offset the income losses of poor households is likely to be prohibitive, especially given falling revenues from reduced economic activity. Continuing to gradually open the economy again will be critical for avoiding permanent job losses and increases in poverty for the coming year. The process of re-opening the economy may also provide opportunities for fostering more private sector-driven and sustainable economic transformation.